Vocational High School Teachers’ Perception of Project-based Learning Method in English Language Teaching: A Case Study - Tanila, Melvira; sulastini, sri; Agustina, imas Wahyu (STAIRS: English Language Education Journal, 2024)
As Vocational High School (VHS) students are prepared to work in certain fields, project-based learning (PjBL)becomes one of the teaching and learning methods that teachers can use to meet the expectations in the work field. Even though the effectiveness of PjBL implementation is related to how the teacher perceives the method, less attention is given to studies that focus on teachers' perceptions of the principles of PjBL. Therefore, this study aimed to investigate the English teachers' perception of the PjBL method in terms of the objectives, principles, and teachers' roles. The descriptive case study was employed as the research design to answer the formulated research questions. Semi-structured interviews with English teachers at SMKN 26 Jakarta were conducted to collect the data. The findings show that all teachers have a good perception of the objectives of the PjBL method. Most teachers fully understand their role in the PjBL method. However, there was some misunderstanding in teachers' perception of the principle of challenging problems/questions and public products. 75% of the teachers did not see sustained inquiry and reflection as the principle of the PjBL method. Therefore, teacher professional development training related to the principles of the PjBL method needs more attention.